PARENTAL FREQUENCIES AND SPATIAL CONFIGURATION SHAPE BUMBLEBEE BEHAVIOR AND FLORAL ISOLATION IN HYBRIDIZING RHINANTHUS. (23rd January 2013) - Natalis, Laurent C.; Wesselingh, Renate A.
Abstract : To shed light on the role played by pollinators in the diversification of angiosperms, focus is needed on how floral isolation varies locally in the early stages of plant divergence. The few studies performed so far have often used species pairs with distinct pollination syndromes and contrasting floral displays. Here, we focus on a hybridizing pair ( Rhinanthus minor and Rhinanthus angustifolius ) with strong similarities in flower morphology and pollinators (bumblebees). We examined how ethological isolation changes locally in relation to relative Rhinanthus frequencies, spatial configurations, and pollinator assemblages. Interestingly, floral divergence based on adaptation to different pollinators is unlikely in Rhinanthus: no relationship was found between floral isolation and the local pollinator assemblage. In contrast, species frequency and spatial arrangement strongly influenced bumblebee behavior, ethological isolation, and thus potentially hybrid formation. When both Rhinanthus were present in equal proportions, bees generally preferred the more rewarding and conspicuous species. However, when the Rhinanthus frequencies were unbalanced, the more abundant species was preferred, although this was less pronounced when the less rewarding R. minor predominated. Ethological isolation is highly sensitive to site characteristics, and can be as high as in species with contrasting floral displays and pollinator suites, even though flowers are similar.